Social competence for students with learning disabilities in English - Khasawneh, Mohamad Ahmad Saleem (Technium Social Sciences Journal, 2021)
The study aimed at investigating the effect of a training program based on extracurricular activities in developing social competence among a sample of students with learning disabilities in the basic stage in Irbid Governorate. The sample consisted of (40) third and fourth-grade students enrolled in the resource rooms. The study sample was divided into two groups; an experimental group (20) students and a control group (20) student. The training program for developing social competence was applied only to the experimental group . The Walker-McConnell Scale of Social Competence-Children version (prepared by "Walker- McConnell", translated into Arabic by Ahmed Awad 2002) was applied to all study members before and after the application of the training program. The statistical analysis of the data resulted in the presence of statistically significant differences at the level of (a less / equal 0.05) between the mean scores of the experimental and control groups on the social competence scale and the total score of the scale, in favor of the experimental group. There were no statistically significant differences at (a less / equal 0.05) between the mean scores of the experimental and control groups on the social competence scale due to the interaction between age and group in the post-test.